Pooled funding and collective borrowing : suggestions for adaptation in the formal financial sector - Birchwood, Anthony ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1997)
Discusses the issue of financing of socially desirable projects especially with respect to the informal sector, with a view of finding alternative credit mechanisms which the formal financial sector can adopt.